"The Paper that you Have in Your Hand is My Freedom": Migrant Domestic Work and the Sponsorship (Kafala) System in Lebanon. Issue 2 (June 2013) - Pande, Amrita
A recent report on migrant domestic work in Lebanon has cited psychological disorder among Lebanese "Madams" as the leading cause of violence against their migrant maids (Jureidini, 2011, www.kafa.org.lb/StudiesPublicationPDF/PRpdf38.pdf ). This report typifies much of the existing scholarship on the experiences of migrant domestic workers (MDWs) in the Middle East, where the focus is on employer–employee relationships, especially the abusive Arab "Madam." In this paper, I argue that the portrayal of violations of MDW rights as abuse of one set of women by another is inherently problematic on several fronts. It privatizes the structural problem of workers' and immigrant rights violations, delegates it to the household, and absolves the state of its responsibility. Moreover, the focus on abusive employers takes attention away from the root of the problem – the inherently exploitative system of migration and recruitment in the region, the sponsorship system. The sponsorship system not only creates conditions for much of these violations, but also systematically produces a new population of readily exploitable worker – the category of "illegal workers." Oral histories and interviews with individual workers are employed to analyze the process by which illegal workers are "produced" in Lebanon. Finally, focus group discussions highlight critical policy recommendations made by the workers themselves, which address the systemic bases of their exploitation in Lebanon.